High-density data recording via laser thermo-lithography and ion-beam etching - Gorbov, I.V.; Kryuchyn, A.A.; Grytsenko, K.P.; Manko, D.Yu.; Borodin, Yu.O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Pits 250 – 300 - nm wide were obtained on the surface of thin organic
nanocomposite film using master-disc laser-burning station with 405 nm laser beam
focused by 0.85 NA lens. The film with obtained pits was used as a mask for subsequent
reactive ion-beam etching of glass substrate. Finally, 150 – 200-nm pits were performed
on the substrate surface. Nanocomposite films were based on organic positive photoresist
with a dye inclusions. This dye is characterized by wide absorption band within the
spectral region 390–410 nm and can be evaporated by laser irradiation with the
wavelength 405 nm